Attraction of Aulacophora foveicollis Lucas (Coleoptera: Chrysomelidae) to Host Plant Cucurbita maxima Duchesne (Cucurbitaceae) Volatiles - Biswanath Bhowmik; Udipta Chakraborti; Alivia Mandal; Bishwajeet Paul; Kakali Bhadra (Agronomy, 2022)
The volatiles extracted by the dynamic headspace collection system from the undamaged and conspecific damaged Cucurbita maxima were analyzed by Gas chromatography–mass spectrometry (GC-MS). The olfactory responses of antennal chemosensilla by male and female A. foveicollis towards the plant volatiles were studied by electroantennography (EAG), while the behavioral responses were analyzed by olfactometer bioassay under laboratory conditions. Scanning electron microscopic study revealed the predominance of antennal olfactory sensilla of seven different types with four types of mechanosensilla. The antennae are sexually dimorphic, with differences in density of the chemosensillae present in the apical band region of segment IX, called the circumferential band, being higher in the females. Female antennae showed maximum peak amplitudes for 2-methyl phenol (at 10 mg/mL), followed by 1,4, dimethoxybenzene (at 5 mg/mL), while male antennae showed maximum amplitudes for heneicosane (at 5 mg/mL). Y-tube bioassays revealed maximum attractiveness towards 1,4, dimethoxy benzene that decreased progressively across heneicosane, pentacosane, tetradecane, ethyl benzene, D-limonene, nonadecane, eicosane, nonanal, decanal, α-pinene, phytol and benzaldehyde in females. However, male species were more responsive towards heneicosane, followed by 1,4 dimethoxybenzene, while the responses to pentacosane and tetradecane were equal, followed by equal responses to decanal, ethyl benzene and nonadecane, and thereafter, a progressively reducing response was observed towards α-pinene, eicosane, nonanal, D-limonene, phytol and benzaldehyde. The study assists in understanding the role of olfaction by A. foveicollis in the host plant Cucurbita maxima by listing compounds that act as potential kairomones for the beetle, and can be expected to facilitate development of an eco–friendly trap and/or by attracting the natural enemies for control of the pest.